A comparison of serum selenium, zinc and copper level in visceral and cutaneous leishmaniasis - Farzin, Leila (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Leishmaniasis is a widespread tropical infection, which has a high incidence rate in Iran. Visceral leishmaniasis (VL) and cutaneous leishmaniasis (CL) are two forms of this disease. In this study, we investigated if selenium (Se), zinc (Zn) and copper (Cu) levels differ in different forms of leishmaniasis. MATERIALS AND METHODS: To determine if leishmaniasis has effects on trace elements status, they were determined by atomic absorption spectrometry (AAS) in patients (n = 155, 95 CL and 60 VL) and control group (n = 100). RESULTS: Our findings indicate that there is a significant difference in the values of Se and Zn between control and patient groups (P < 0.0001 and P < 0.001, respectively). Se and Zn levels were 3.65 ± 0.88 and 67.24 ± 18.76 μg/dL in the leishmaniasis patients, and these values were observed to be statistically lower compared to the control groups (11.10 ± 2.37 and 119.61 ± 26.18 μg/dL, respectively). Meanwhile, no significant difference in status of Cu was found between the cases (110.55 ± 29.25 μg/dL) and healthy subjects (91.42 ± 27.54 μg/dL) (P > 0.05). When the patients were divided into two groups, there appeared to be a significant decrease (P < 0.001) in Se concentration for VL patients (2.57 ± 0.64 μg/dL) compared with CL patients (4.33 ± 1.06 μg/dL). CONCLUSION: Based on these results, serum Se and Zn levels could be a useful marker for the pathophysiology of leishmaniasis.